Ultrasonographic evaluation of cervical length and amniotic fluid index as predictor of pregnancy outcome in cases of preterm premature rupture of membrane - Nidhi Gupta; Mohita Agarwal; Akanksha Gupta; Neha Shamshi (Asian Journal of Medical Sciences, 2022)
Background: Amniotic fluid index (AFI) and cervical length (CL) can be used to predict delivery latency, maternal, and neonatal outcome in cases of preterm premature rupture of membrane (PPROM). Aims and Objectives: The aims of this study were to study the AFI and CL as a predictor of pregnancy outcome in cases presenting with PPROM, to determine the AFI in cases presenting with PPROM, to determine CL ultrasonographically in cases presenting with PPROM, and to measure the efficacy of these parameters as a predictor of pregnancy outcome in cases presenting with PPROM. Materials and Methods: This was an ambispective observational study conducted from November 2019 to July 2021 in the Department of Obstetrics and Gynecology in S. N. Medical College, Agra. A total of 100 women with singleton pregnancy and vertex presentation who presented to hospital within 12 h of spontaneous rupture of membrane (PPROM) from period of gestation 28–34+6 weeks were enrolled in this study. Results: Delivery latency was inversely related to period of gestation at pprom (P<0.0001). Mean AFI in Group 1 was 5.15 cm and in Group 2 was 7.12 cm and the difference between both group was statistically significant (P<0.0001). Thus, our study shows positive correlation between AFI and delivery latency. Mean transvaginal CL (TVCL) in Group 1 was 2.47 cm and in Group 2 was 2.99 cm. Difference in terms of TVCL between both the groups was found to be statistically significant (P=0.00005). Need for neonatal intensive care unit admission was higher in Group 1 than Group 2 and this difference was statistically significant (P=0.020). Conclusion: Our study shows that there was an increase in positive predictive value when we combine AFI and TVCL in prediction of delivery latency, so women with AFI ≤5 and TVCL ≤2.5 cm had 85.6% risk of delivery within 7 days after PPROM. A long CL (TVCL >2.5 cm) and AFI >5 correlated with increased delivery latency and increased risk of maternal morbidity (chorioamnionitis, abruption, and cord prolapse).